2003
DOI: 10.1021/ja037315+
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive High Resolution Inverse Detection NMR Spectroscopy of Proteins in the Solid State

Abstract: A new indirect detection scheme for obtaining (15)N/(1)H shift correlation spectra in crystalline proteins is described. Excellent water suppression is achieved without the need for pulsed field gradients, and using only a 2-step phase cycle. Careful attention to overall NMR instrument stability was found critical for obtaining the best resolution and sensitivity. Magnetic dilution by deuteration of the protein in combination with high-speed magic angle spinning produces (1)H resonances averaging only 0.22 ppm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
221
0
4

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(233 citation statements)
references
References 25 publications
8
221
0
4
Order By: Relevance
“…The strong proton dipolar coupling problem has been addressed with two approaches: (1) diluting the proton bath, (2) spinning fully protonated samples at ~40 kHz. The first approach yields very high resolution [8][9][10][11], and 1 H-1 H distance restraints as long as 9 Å have been detected, enabling the determination of a high-resolution protein structure [12]. The second approach is important for systems such as membrane proteins where deuteration and back-exchange may be challenging; it also permits all non-exchangeable protons to be investigated in a single experiment [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strong proton dipolar coupling problem has been addressed with two approaches: (1) diluting the proton bath, (2) spinning fully protonated samples at ~40 kHz. The first approach yields very high resolution [8][9][10][11], and 1 H-1 H distance restraints as long as 9 Å have been detected, enabling the determination of a high-resolution protein structure [12]. The second approach is important for systems such as membrane proteins where deuteration and back-exchange may be challenging; it also permits all non-exchangeable protons to be investigated in a single experiment [13].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore the water resonance is more than 10,000 times stronger than a 13 C or 15 N-edited protein proton resonance; thus water and other solvent signals must be suppressed by four orders of magnitude to utilize the full receiver dynamic range for the protein signals. Previously reported solvent suppression schemes yield suppression by two to three orders of magnitude for a single resonance line (such as water), achieved by employing either pulsed field gradients (PFGs) [9] or saturation pulses [10]. We had extended the method of Paulson and Zilm [10] to achieve simultaneous suppression of multiple solvent signals, by using a long, moderate-power saturation pulse [13].…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18] One such study by Paulson et al showed that nanocrystalline sample preparations of ubiquitin yielded three different sets of 1 H- 15 N correlation spectra, resulting from three different polymorphs. 10 Subsequently Siedel et al assigned the C', CA and CB chemical shifts for two of these polymorphs. 11 Both of these studies focused on chemical shift differences among the backbone resonances.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high content of water in FROSTY samples, suppression of the water resonance was achieved by implementing a pulse train of 4×15 ms with a rf field strength of 4-10 kHz and alternating phase during longitudinal 15 N magnetization. [11,12] The 2D 1 H-15 N (and 3D hCXhNH experiments adapted from [13,14] ) were designed in a constant-time fashion here to ensure reproducible dephasing of the water resonance as well as to yield optimal signal-to-noise ratios. Transmitters were placed at 4.7 ppm ( 1 H) and 119 ppm ( 15 N), respectively.…”
Section: Nmr Spectroscopy and Data Analysismentioning
confidence: 99%